Competition of Mobile Banking Service Quality of Syariah Banking in the Digital Era - Nurul Khomariyah; Asyari Hasan (Universitas KH. Abdul Chalim Mojokerto, 2024)
The increasing competition in the Indonesian Islamic banking industry has encouraged many Islamic banks to improve the quality of service to customers by utilizing the rapid development of information technology. The study aims to analyze the competition in Mobile Banking Service Quality that occurs at Bank BSI and Bank Muamalat. This study uses an associative-comparative research type with a quantitative approach. The data source used for this study is primary data. The data collection technique used is a questionnaire with the number of samples was 100 respondents. The data analysis technique used in this study is simple linear regression analysis. The results obtained from the current study indicate that the service quality of mobile banking has a positive and significant influence on customer satisfaction at Bank BSI and Bank Muamalat. There is a difference in the quality of mobile banking services towards customer satisfaction between Bank BSI and Bank Muamalat with respective values ​​of 62.07 (62%) and 38.39 (38%). This shows that the quality of Bank BSI's mobile banking services is higher in customer satisfaction.